DEFERRED TAX ASSETS IN FOCUS: ANALYZING THEIR EFFECT ON EARNINGS MANAGEMENT WITH AUDIT QUALITY AS A KEY MODERATOR - Benny Oktaviano; Dhani Rosjadi; Dian Sulistyorini Wulandari (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study aims to examine the effect of Deferred Tax Assets (DTA) on Earnings Management and assess the role of Audit Quality as a moderating variable. The research object comprises manufacturing firms listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. A quantitative approach was employed, using panel regression with a Random Effects model, selected based on Hausman and Lagrange Multiplier tests. The results indicate that DTAs have a positive and significant effect on Earnings Management, suggesting that firms use DTA flexibility to manipulate earnings. However, the interaction test between DTA and Audit Quality yields a negative but statistically insignificant coefficient, indicating that Audit Quality does not significantly moderate the relationship between DTA and Earnings Management. These findings imply that, although high-quality auditors are expected to constrain earnings management practices, their moderating role was not empirically supported in this sample.